PELESTARIAN KESENIAN KETOPRAK SEBAGAI UPAYA MENINGKATKAN KECINTAAN BUDAYA - Hidayah, Ela Nurul; Roziqin, Muhammad Reza Ahsan; Ediani, Nabilla Nilawati Putri; Faradilla, Ratna Lutfia; Agustina, Shinta; Apriliana, Sinta; Alviana, Tasya Nurisma; Lestariningrum, Anik (Jurnal Pengabdian Masyarakat Indonesia, 2024)
The challenge to preserve culture, especially traditional arts, is increasingly complex due to changing times and the impact of globalization that is getting stronger in the current era. The development of the times and the flow of globalization have caused many changes in people's lives, which also have an impact on the sustainability of local culture. Based on observations and interviews conducted, Ringinanom Village needs assistance in preserving traditional arts, one of which is ketoprak. The purpose of implementing community service activities is to know and increase regeneration or awareness of traditional ketoprak art. The stages of community service activities are carried out from the preparation stage, planning stage and implementation stage. The preparation stage is carried out with an approach with socialization about the preservation of ketoprak cultural arts, the KKN team analyzes residents who have potential and coordinates with the parties who will be involved. The planning stage is carried out from the data analysis stage based on observations made. The implementation stage is carried out according to the results of information obtained from the planning stage. The results of the activity received a positive response which showed that the maximum activity target was achieved.